Melodične in harmonske tonske strukture v orkestralnih skladbah Demetrija Žebreta - Salmič Kovačič, Karmen (Muzikološki zbornik, 2007)
This analytical article on music deals with the variation of melodic and harmonic tone structures and their reciprocal effects in eight orchestral pieces by Demetrij Žebre - a student of Slavko Osterc and one of the moderately modernistic creative authors of Slovene orchestral music in the first half of the 20th century. The analysis shows that in Žebre's music old meets new in various ways. The elements of the old tonality are mostly included within a new texture, sound, movement structure and rhythmically metrical combinations in several different manners. The compositions from the composer's period of pursuit of more radical solutions in terms of deviation from tonality almost reach the boundaries of a disoriented atonality without an attempt of their dodecaphonic organization.
Keywords: 20st.; glasbene analize; melodika in harmonija; orkestralna glasba; slovenska glasba; Žebre, Demetrij, 1912-1970